1977
DOI: 10.1073/pnas.74.8.3587
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of somatostatin-like immunoreactivity in some peripheral sympathetic noradrenergic neurons

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
83
1

Year Published

1980
1980
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 344 publications
(86 citation statements)
references
References 35 publications
2
83
1
Order By: Relevance
“…In the coeliac-superior mesenteric ganglion complex of the guinea pig, the NA/somatostatin (11) (13), it may be suggested that these VIP nerves, together with the NA/somatostatin (in the guinea pig) and the NA (in the cat) neurons, are part ofthe reflex arcs between the mid-and distal gut and prevertebral ganglia (30,31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the coeliac-superior mesenteric ganglion complex of the guinea pig, the NA/somatostatin (11) (13), it may be suggested that these VIP nerves, together with the NA/somatostatin (in the guinea pig) and the NA (in the cat) neurons, are part ofthe reflex arcs between the mid-and distal gut and prevertebral ganglia (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis has revealed-that some of these peptides coexist with classical transmitters in sympathetic neurons. Thus, some peripheral noradrenergic cell bodies in sympathetic ganglia of the guinea pig, particularly prevertebral ganglia, contain a somatostatinlike peptide (11). An avian pancreatic polypeptide (APP)-like peptide has been demonstrated in a population of peripheral noradrenaline neurons (12).…”
mentioning
confidence: 99%
“…The presence of two or more putative transmitters in the same mature neuron has been documented in invertebrates (Kerkut et al 1967, Brown stein et al 1974, but see also Osborne 1977 and in the mammalian periph eral (Hokfelt et al 1977a) and central nervous system (Chan-Palay et al 1978, Hokfelt et aI 1978b. In several nuclei of the lower medulla oblongata in the rat, there are neurons that contain either 5-HT or SPLI, or both 5-HT and SPLI (Chan-Palay et aI 1978, Hokfelt et aI 1978b.…”
Section: Substance P and 5-hydroxytryptamine Coexist In Some Medullarmentioning
confidence: 99%
“…[42] Most neurons are noradrenergic and supply the stomach, spleen, pancreas, small intestine and mesen-teric blood vessels. [43] In the current study, we identified small, medium and large sized neurons. Such neuronal population has earlier been functionally divided into pilomotor, vasomotor and secretomotor neurons.…”
Section: Discussionmentioning
confidence: 99%